Progress toward standardized diagnosis of vascular cognitive impairment: Guidelines from the Vascular Impairment of Cognition Classification Consensus Study. Issue 3 (19th October 2017) - Skrobot, Olivia A.; Black, Sandra E.; Chen, Christopher; DeCarli, Charles; Erkinjuntti, Timo; Ford, Gary A.; Kalaria, Rajesh N.; O'Brien, John; Pantoni, Leonardo; Pasquier, Florence; Roman, Gustavo C.; Wallin, Anders; et al.
Abstract: Introduction: Progress in understanding and management of vascular cognitive impairment (VCI) has been hampered by lack of consensus on diagnosis, reflecting the use of multiple different assessment protocols. A large multinational group of clinicians and researchers participated in a two‐phase Vascular Impairment of Cognition Classification Consensus Study (VICCCS) to agree on principles (VICCCS‐1) and protocols (VICCCS‐2) for diagnosis of VCI. We present VICCCS‐2. Methods: We used VICCCS‐1 principles and published diagnostic guidelines as points of reference for an online Delphi survey aimed at achieving consensus on clinical diagnosis of VCI. Results: Six survey rounds comprising 65–79 participants agreed guidelines for diagnosis of VICCCS‐revised mild and major forms of VCI and endorsed the National Institute of Neurological Disorders–Canadian Stroke Network neuropsychological assessment protocols and recommendations for imaging. Discussion: The VICCCS‐2 suggests standardized use of the National Institute of Neurological Disorders–Canadian Stroke Network recommendations on neuropsychological and imaging assessment for diagnosis of VCI so as to promote research collaboration.